Faktor-Faktor Yang Berpengaruh Terhadap Tingkat Pengungkapan Risiko Pada Perusahaan Perbankan - Hanny, Liana Susanto (Jurnal Paradigma Akuntansi, 2021)
This research was conducted with the aim of obtaining empirical evidence regarding the effect of profitability, leverage, and company size on the level of risk disclosure in banking companies listed on the Indonesia Stock Exchange (BEI) for the period of 2016-2018. This research was conducted using panel data and the method used in testing the hypothesis was the multiple linear regression method. The sample selection technique used was purposive sampling technique using 27 banking companies as research samples. The data used in this study are secondary data in the form of financial statements. The results of this study indicate that only firm size has a positive effect on the level of risk disclosure, while profitability and leverage have no effect on the level of risk disclosure.